Water Resources and Their Suitability for Irrigation in Khabat District - Tahseen Abdulrahem Azeez; Karzan Ahmad Abdulwahid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The suitability of water resources for irrigation is one of the important topics in studies that are related to water resources. The aim of this research is the determination of the water resources and their suitability in Khabat district The main source of water resource in the study region is the water of the Great Zab River. The annual received quantity of water at the (Efraz Station) reaches up to (8.56) m3. There is also a number of (437) water wells, (2) fountains and (3) water springs that were dug for irrigation purposes. The study has reached a conclusion based on the measurements and classifications that were made to decide the suitability of water for irrigation operations by the concentration of ions (dissolved salts, magnesium, chloride, ph, and nitrate) and classifications (Todd, Wilcox, Ussl, SAR, FAO, Altoviski, Diagram, Richards) hence, declared that most of the water resources in the study region (surface and ground water) are suitable for irrigation and watering animals.